Implementasi Saving Energy Protokol Dynamic Source Routing (DSR) pada Mobile Ad Hoc Network (MANET) dengan Metode Sleep Mode - Firza Nur Hibatullah; Primantara Hari Trisnawan; Rakhmadhany Primananda (Fakultas Ilmu Komputer (FILKOM), Universitas Brawijaya, 2020)
Mobile ad hoc network (MANET) is a collection of wireless mobile nodes that are connected through radio waves without a central access point, free moving nodes, and dynamic. But this kind of network still has several problems, power consumption is one of the most important design problems in MANET as a node on MANET that has a limited battery. Based on the problems described earlier, we need a concept of implementing energy saving on MANET and analyzing the effect of energy on protocol performance when reducing energy consumption. This study compares the implementation of the concept of saving energy using the sleep mode method with protocol performance, namely Packet Delivery Ratio (PDR), packet loss, and average residual energy using Network Simulator 2 (NS2) in the Destination Source Routing (DSR) protocol. Testing is done by making sleep mode implemented and without the implemented sleep mode for the variation of the total node and data rate. This research successfully implemented the concept of energy saving in the DSR protocol in MANET with the sleep mode method. How to implement energy saving on the system is to configure the source code protocol by changing the MAC protocol using Sensor MAC (S-MAC) and writing the source code to enable the sleep mode feature. This study concluded that the performance of the DSR routing protocol without implementing a sleep mode was an average of 87.5% better than the implementation of sleep mode on the testing parameters of PDR values and packet loss. However, the DSR routing protocol with the implementation of sleep mode was better on average 91.67% than without the implementation of sleep mode on the testing parameters of average residual energy.